PENGARUH ARTIFICIAL AGING DAN NATURAL AGING TERHADAP KEKERASAN DAN STRUKTUR MIKRO PENGECORAN LOGAM PISTON Al-Si - Edriyanto, Edriyanto; Balaka, Ridway; Aminur, Aminur (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2017)
The purpose of this research is to know the effect of artificial aging and natural aging on increasing hardness and micro structure of Al-Si alloy recycling. The material used in this research is Al-Si alloy which comes from motorcycle piston scrap which is casted like piston (prototype). The casting method used is acasting wherein a liquid metal is poured into a mold without pressure. Piston scrap is melted with 700????C temperature, on induction furnace for 1 hour and poured into die casting. Product of castings of prototype motorbike piston are prepared to be specimen followed by artificial aging and natural aging process with holding time 1-3 hour to test micro structure and hardness test of vickers method.Vickers hardness test results show that the maximum hardness value of aritifiacial aging specimens is 132,16 Kg / mm² with 3 hours hold time, and the lowest hardness value is 110,31 Kg / mm² with 1 hour hold time. While for themaximum hardness value of natural aging samples is 101,57 Kg / mm² with 3 hour hold time, while the lowest hardness value is obtained equal to 82,53 Kg / mm². With result of observation of micro structure of each sample undergoes structure change.Keywords: Metal casting, natural aging, artificial aging, hardness, and micro struktur.